2016
DOI: 10.1074/jbc.m115.708263
|View full text |Cite
|
Sign up to set email alerts
|

The Dimeric Architecture of Checkpoint Kinases Mec1ATR and Tel1ATM Reveal a Common Structural Organization

Abstract: The phosphatidylinositol 3-kinase-related protein kinases are key regulators controlling a wide range of cellular events. The yeast Tel1 and Mec1·Ddc2 complex (ATM and ATR-ATRIP in humans) play pivotal roles in DNA replication, DNA damage signaling, and repair. Here, we present the first structural insight for dimers of Mec1·Ddc2 and Tel1 using single-particle electron microscopy. Both kinases reveal a head to head dimer with one major dimeric interface through the N-terminal HEAT (named after Huntingtin, elon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 63 publications
5
36
0
Order By: Relevance
“…The internal symmetry observed is most likely created by the Rad26 dimer that positions two opposing binding sites for Rad3 that are rotated 180°relative to each other. A very similar dimeric architecture was recently observed in a 3D reconstruction of the orthologs complex in yeast Mec1-Ddc2 (16). Based on the combined data, it is possible to suggest a model of how Rad3-Rad26 assembles into a heterotetrameric complex, in which the Rad26 dimer is the central scaffold binding two molecules of Rad3 through their HEAT domains (Fig.…”
Section: Proposed Model For a Heterotetrameric Rad3-rad26 Complexsupporting
confidence: 74%
“…The internal symmetry observed is most likely created by the Rad26 dimer that positions two opposing binding sites for Rad3 that are rotated 180°relative to each other. A very similar dimeric architecture was recently observed in a 3D reconstruction of the orthologs complex in yeast Mec1-Ddc2 (16). Based on the combined data, it is possible to suggest a model of how Rad3-Rad26 assembles into a heterotetrameric complex, in which the Rad26 dimer is the central scaffold binding two molecules of Rad3 through their HEAT domains (Fig.…”
Section: Proposed Model For a Heterotetrameric Rad3-rad26 Complexsupporting
confidence: 74%
“…( d ) Model of ATR activation. ATR–ATRIP forms a dimer of dimers 167 . TOPBP1 or ETAA1 AAD binding likely induces a conformational change in ATR that reduces the Km of ATR for its substrates and thereby activates ATR 168 .…”
Section: Figurementioning
confidence: 99%
“…Mec1 Autophosphorylation at Site S1964 Can Occur in trans Recent structural studies have suggested that budding yeast Mec1-Ddc2 exists as a homodimer of a heterodimer (Sawicka et al, 2016;Wang et al, 2017). Autophosphorylation of Mec1 could, therefore, happen in cis or in trans.…”
Section: Mutational Analysis Of Sq/tq Sites In Mec1mentioning
confidence: 99%
“…Under basal conditions, most Mec1 exists as a homodimer of a heterodimer with its binding partner Ddc2 ATRIP (Ball and Cortez, 2005;Sawicka et al, 2016). Upon induction of a DSB, the double-stranded DNA (dsDNA) ends are resected and coated with the single-stranded DNA (ssDNA) binding protein RPA (Alani et al, 1992;Zou and Elledge, 2003).…”
Section: Introductionmentioning
confidence: 99%